Characterization of the Powdery Mildew Resistance Gene in the Elite Wheat Cultivar Jimai 23 and Its Application in Marker-Assisted Selection - Jia, Mengshu (Front Genet, 2020)
Powdery mildew infection of wheat (Triticum aestivum L.), caused by Blumeria graminis f. sp. tritici (Bgt), is a destructive disease that threatens yield and quality worldwide. The most effective and preferred means for the control of the disease is to identify broad-spectrum resistance genes for breeding, especially the genes derived from elite cultivars that exhibit desirable agronomic traits. Jimai 23 is a Chinese wheat cultivar with superior agronomic performance, high-quality characteristics, and effective resistance to powdery mildew at all growth stages. Genetic analysis indicated that powdery mildew resistance in Jimai 23 was mediated by a single dominant gene, tentatively designated PmJM23. Using bulked segregant RNA-Seq (BSR-Seq), a series of markers was developed and used to map PmJM23. PmJM23 was then located at the Pm2 locus on the short arm of chromosome 5D (5DS). Resistance spectrum analysis demonstrated that PmJM23 provided a broad resistance spectrum different from that of the documented Pm2 alleles, indicating that PmJM23 is most likely a new allele of Pm2. In view of these combined agronomic, quality, and resistance findings, PmJM23 is expected to be a valuable resistance gene in wheat breeding. To efficiently use PmJM23 in breeding, the closely linked markers of PmJM23 were evaluated and confirmed to be applicable for marker-assisted selection (MAS). Using these markers, a series of resistant breeding lines with high resistance and desirable agronomic performance was selected from the crosses involving PmJM23, resulting in improved powdery mildew resistance of these lines.